Nazwy puste u Tadeusza Kotarbińskiego - Horecka, Aleksandra (Filozofia Nauki, 2007)
The paper deals with the concept of empty name in the theory of Tadeusz Kotarbiński - one of the representatives of Lvov-Warsaw School. The aim of the article is to reconstruct Kotarbinski's definition of empty names, his thesis concerning structure and connotation of empty names, his interpretation of categorical sentence with empty names and to point out problems which arise in consequence of these theories. Only same expressions regarded traditionally as empty names are empty names according to Kotarbinski, e.g. "son of childless mother" or "centaur". Expressions like "Brotherhood of the sons of childless mother" - in opinion of Kotarbiński - aren't names at all, they are onomatoids. In Kotarbiński's syntactic-semantic definition of empty name several vicious circles can be found. His theories of empty names and their connotation are at odds with his thesis of reism. He doesn't make any distinction between different types of empty names, but he prompts to distinguish three types of such names: (1) names of objects the non-existence of which is known by experience and names of such non-existing objects, which could exist in the past, (2) names of incoherent objects and (3) names of objects, which can exist in future. The semantic definition of empty names consistent with reism is possible on condition that empty names are only the names of objects that will exist in future.